The Urgence of Teacher's Example for Student Education in School - Abid Nurhuda; Yulita Putri (Journal Corner of Education, Linguistics, and Literature, 2023)
Education is designed to form students who have high moral ethics and character both individually and socially. The character of the students themselves can be formed by the teacher through the way of speaking, tolerance, conveying material and example while at school. In addition, technology has also contributed to the news lately ranging from oppression, hostility, to bringing each other down. The problem describes the phenomenon of moral decline which is very concerning, so that a solution is needed, one of which is the exemplary attitude of the teacher to his students. So the purpose of this study is to describe the urgency of teacher exemplary for student education in schools. The method used is qualitative with a literature study approach followed by documentation techniques when data collection is then analyzed and finally concluded. The results of the study indicate that the Urgency of Teacher Exemplary for Student Education in Schools is more dominant in instilling their character either directly (formally) from words, actions and ways of dressing or indirectly (non-formally) starting from wisdom, tolerance, to sincerity.